2015
DOI: 10.1159/000438569
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxybutyrate Facilitates Fatty Acids Synthesis Mediated by Sterol Regulatory Element-Binding Protein1 in Bovine Mammary Epithelial Cells

Abstract: Background/Aims: In dairy cows, β-hydroxybutyrate (BHBA) is utilized as precursors of de novo synthesized fatty acids in mammary gland. Ketotic cows are characterized by excessive negative energy balance (NEB), which can further increase the blood BHBA concentration. Sterol regulatory element-binding protein1 (SREBP1) and cell death-inducing DNA fragmentation factor-alpha-like effector α (Cidea) play crucial roles in lipid synthesis. Therefore, we hypothesized that BHBA could stimulate SREBP1/Cidea pathway to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Work in nonruminants has indicated that CIDEA could regulate the expression of FASN and ACACA in the liver and adipose tissue (Zhou et al, 2012;Zhang et al, 2015). In the present study, overexpression of CIDEA increased the abundance of FASN and ACACA and increased TAG content in bovine mammary epithelial cells, indicating some control over the expression of FASN and ACACA.…”
Section: Discussionsupporting
confidence: 62%
“…Work in nonruminants has indicated that CIDEA could regulate the expression of FASN and ACACA in the liver and adipose tissue (Zhou et al, 2012;Zhang et al, 2015). In the present study, overexpression of CIDEA increased the abundance of FASN and ACACA and increased TAG content in bovine mammary epithelial cells, indicating some control over the expression of FASN and ACACA.…”
Section: Discussionsupporting
confidence: 62%
“…4B ). Treatment of cultured mammary epithelial cells with BOHB activates SREBF1 and increases the secretion of triacylglycerol 28 . These cell culture models might explain at least one mechanism by which NEB increase the fat content of cows’ milk.…”
Section: Resultsmentioning
confidence: 99%
“…In dairy cows, elevated levels of circulating ketone bodies are associated with an elevated percentage of fat in the milk 28 . In ruminants, BOHB is the main precursor of milk fat synthesis 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The RNA was reverse-transcribed to cDNA with the reverse transcription kit (TaKaRa Biotechnology Co., Ltd., Tokyo, Japan) according to the supplier's protocol. The relative expression of the target genes was determined by the 2 -ΔΔCT method [22]. β-actin mRNA was used as an internal control.…”
Section: Rna Extraction and Real-time Quantitative Pcr (Qrt-pcr)mentioning
confidence: 99%